THE IMPORTANCE OF PEDAGOGICAL EXPERIMENTS IN TEACHING ECONOMETRICS TO STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Ravshanova Muhayyo Maxmanazarovna (American Journals, 2024)
This article is devoted to the process of conducting a pedagogical experiment in teaching econometrics. In the article, the author also provided information on the types of pedagogical experiments, the results of the experiment, as well as the conclusions and proposals made on its basis.
Keywords: Pedagogic experiment, econometrics, experiment, criterion Feshira, validation experiment, technology, methodical system, obrazovanie, pedagogic management.